PEMERTAHANAN BAHASA BUGIS DALAM RANAH KELUARGA DI NEGERI RANTAU SULAWESI TENGAH (The Buginese Language Preservation of Family Domain in Central Sulawesi Land) - Tamrin Tamrin (SAWERIGADING, 2014)
The survival of a local language isthe symbol of the viability concept of traditional culture values. The lossor extinction of the local language including Buginese language, means the loss and the extinction of theconcept of traditional culture values because the traditional culture only could be understood better throughthe local language expressed by the society. In the other words, if the local language is extinct, the imageand the identity of the society become unclear. By discussing the case of Buginese language preservation inCentral Sulawesi land, it aims at (1) describing the ways of Buginese language preservation of family domainin Central Sulawesi and (2) analyzing the factors supporting the Buginese language preservation in CentralSulawesi. The method used in this research is sociolinguistic approach by using interview, observation, andrecording techniques. Then, the data will be analyzed based on percentage of the usage patterns of Bugineselanguage in the family domain. The result of the analysis shows that Buginese people in Central Sulawesi landstill maintain their language in the family domain whether it is viewed from the categories of age, gender,education, and occupation. Factors that support the Buginese language preservation in Central Sulawesi areloyality, the awareness of language norms, the language pride, age, and occupation.